The Effect of Self-Efficacy on Entrepreneurial Intentions Through Subjective Norms Among Business Administration Students at Universities in Sukabumi City - Silla Prasasti; Erry Sunarya; Tetty Sufianty Zafar (Dinasti Publisher, 2025)
This study aims to analyze the effect of self-efficacy on entrepreneurial intention with subjective norms as a mediating variable among business administration students at universities in Sukabumi City. A quantitative approach was used with a survey method targeting students at Muhammadiyah University Sukabumi and Sukabumi Polytechnic. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that self-efficacy has a positive and significant effect on entrepreneurial intention. Additionally, subjective norms were found to significantly mediate the relationship between self-efficacy and entrepreneurial intention. These findings confirm that students' confidence in their entrepreneurial abilities can increase their entrepreneurial intentions, especially when supported by positive social norms from their surroundings. This study has implications for higher education institutions in designing psychological and social-based entrepreneurship development programs to encourage the emergence of young entrepreneurs.